1973
DOI: 10.1172/jci107491
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of Plasmin Digests of Human Growth Hormone in the Rat and Man

Abstract: A B S T R A C T As a first step in our study of structurefunction relationships among primate and non-primate growth hormones, human growth hormone (hGH) was subjected to the limited digestive activity of human plasmin. The lyophilized whole digest, containing less than 2% of unchanged hormone, had an average of 2. The digest also caused glucosuria in partially pancreatectomized rats treated with dexamethasone.These metabolic actions of plasmin-digested hGH in the array of animal tests were confirmed by compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1

Year Published

1974
1974
1991
1991

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 32 publications
0
13
1
Order By: Relevance
“…Bewley et al, furthermore, did not observe increased activity of RCAM-hGH in the tibia test (6). Moreover, we have not observed increased activity of PD-hGH, RCAM-hGH, or PD-RCAM-hGH in promoting uptake of thymidine into rat costal cartilage, another process related to bone growth (5,9). Thus, we are not able to relate the present observations on augmented P retention by RCAM-hGH and PD-RCAM-hGH in man to the enhanced potency of PDhGH in the rat tibia assay.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Bewley et al, furthermore, did not observe increased activity of RCAM-hGH in the tibia test (6). Moreover, we have not observed increased activity of PD-hGH, RCAM-hGH, or PD-RCAM-hGH in promoting uptake of thymidine into rat costal cartilage, another process related to bone growth (5,9). Thus, we are not able to relate the present observations on augmented P retention by RCAM-hGH and PD-RCAM-hGH in man to the enhanced potency of PDhGH in the rat tibia assay.…”
Section: Discussioncontrasting
confidence: 51%
“…It is tempting to speculate that the increased retention of phosphorus seen in man with RCAMhGH and its plasmin digest is related to the enhanced activity of plasmin digests of native hGH (PD-hGH) when assayed in the rat by the tibia test (17)(18)(19). However, such digests do not cause increased phosphorus retention in man (5). This effect is first seen in man when native hGH is reduced and carbamidomethylated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods used have been described in detail (11). In vitro insulin-like activity was assessed by measuring the ability of the hormone preparations to stimulate D-[U-14C]glucose oxidation to 14CO2 by isolated epididymal adipose tissue of hypophysectomized rats (Charles River Breeding Laboratories) weighing approximately 100 g. The details of the procedure have been described (16). RESULTS Because of the similarities in size and properties of native 22-kDa hGH and 20-kDa hGH, it has been quite difficult in the past to isolate 20-kDa hGH from pituitary extracts in a form free of contamination with small amounts of 22-kDa hGH and other pituitary hormones.…”
mentioning
confidence: 99%
“…Later, Yadley and Chrambach (3) described in detail that digestion of HGH with plasmin leads to a progressive transformation of the hormone to various components of higher electrophoretic mobility and increased prolactin activity. Reagan et al (4) and Mills et al (5) reported that hydrolysis of HGH with plasmin did not impair metabolic effects in the rat or in man. A detailed chemical and physical characterization of the cleaved products of HGH by plasmin digestion was not given in any of these studies.…”
mentioning
confidence: 99%